Exofocal dopaminergic degeneration as antidepressant target in mouse model of poststroke depression - Kronenberg, Golo D.; Gass, Peter (Biological psychiatry, 2012)
Background: Although poststroke depression (PSD) is a frequent chronic complication of stroke with high relevance for outcome and survival, underlying pathomechanisms remain inadequately understood. This may be because suitable animal models are largely lacking and existing models are poorly characterized. Methods: Male 129/SV mice were subjected to 30-min middle cerebral artery occlusion (MCAo)/reperfusion and serial magnetic resonance imaging scans. A subset of animals received selective serotonin reuptake inhibitor citalopram starting 7 days after MCAo. Behavioral assessment was performed at 14 weeks. To identify biological correlates of PSD, we quantified corticosterone levels in serum and brain-derived neurotrophic factor levels in brain. The integrity of the mesolimbic dopaminergic system was assessed using tyrosine hydroxylase and dynorphin in situ hybridizations as well as dopamine transporter autoradiography. Results: Left, but not right, MCAo, elicited anhedonia and increased anxiety and despair. This depression-like syndrome was associated with alterations in the mesolimbic reward system. MCAo resulted in delayed degeneration of dopaminergic neurons in ipsilateral midbrain, which was accompanied by reduced dopamine concentrations and decreased levels of dopamine transporter density along with increased brain-derived neurotrophic factor protein levels in ischemic striatum and increased dynorphin messenger RNA expression in nucleus accumbens. Chronic antidepressant treatment initiated as late as 7 days after stroke reversed the behavioral phenotype, prevented degeneration of dopaminergic midbrain neurons, and attenuated striatal atrophy at 4 months. Conclusions: Our results highlight the importance of the dopaminergic system for the development of PSD. Prevention of secondary neurodegeneration by antidepressants may provide a novel target for subacute stroke therapy.